Florística e ecologia de musgos (Bryophyta) na Floresta Nacional de Silvânia, Goiás - Porfirio Junior, Eder Dasdoriano (2010)
Facilitation is an important ecological process, however, still little studied for biological communities. Recently ecology re-examined the positive effects between species and such area has being the focus of ongoing studies and research worldwide. Mosses (Bryophyta) have ecological particularities that make the group a good indicator of micro-and microclimatic changes. However there are few studies aimed to identify patterns of ecological groups in Brazil are still limited and more studies addressing the ecology of bryophytes in the Brazilian Cerrado. It is known that the cerrado has a mosaic of vegetation types ranging from savanna and forest. And that this gradient presents great variability of factors such as occurring species, temperature, humidity and light incidence. Faced with this panorama, this study sought to relate how communities of mosses in areas of cerrado sensu stricto respond to the occurrence of Syagrus flexuosa. The study took place in the Floresta Nacional de Silvania initially the mosses were collected from all the faces in this Conservation Area. Were subsequently selected 50 plots measuring 25 square meters (5x5m) randomly distributed in the cerrado sensu stricto. Data were collected from plots of temperature, coverage of Syagrus flexuosa, humidity, distance from plot to nearest forest formation, diversity, richness and moss substrates occurring in the plots. Cover classes were created in S. flexuosa, Class I shares with coverage less than or equal to 33% of the share by S. flexuosa Class II shares with coverage exceeding 33% and less than 66% and Class III shares with coverage greater than or equal to 66% by Syagrus flexuosa. We found through an analysis of variance (ANOVA) decrease in temperature in the plots with higher cover of S. flexuosa (F2, 47 = 42.73, p <0.001). The relative decrease in measured temperature between the classes was 3 ° C between classes I and III, indicating that the coverage of S. flexuosa acted effectively in temperature. Analysis of variance (ANOVA) to relate the classes of coverage and richness of mosses found in the plots indicated that portions of Class I and II had similar richness and portions of Class III have a wealth on average, four times greater (F2, 47 = 38.87, p <0.001). The ANOVA performed between the classes of coverage and the abundance of mosses showed a similar pattern to the richness and abundance of mosses found a much larger plots of Class III (F2, 47 = 43.57, p <0.0001). The linear regressions performed using the distance between the plots and the forest was negatively related to wealth and diversity of species. The occurrence of mosses Fabronia ciliaris var. polycarpa, Pilotrichella flexilis and Syrrhopodon ligulatus occurred only in plots with high coverage of Syagrus flexuosa and generally about the area of interference of the palm. Species of shade Pilotrichella flexilis and Syrrhopodon ligulatus were found mainly in the installments of Classes II and III. The forms of life found in the plots were also mostly those considered resistant to desiccation (cushion and tuff) 65%, however 89% of the occurrences of life forms less resistant to desiccation (frame and mat) occurred in plots with greater coverage S. flexuosa. Studies comparing more restricted areas of savanna are required so that data can be compared and define the absence or presence of patterns.